2016
DOI: 10.1152/ajpheart.00010.2016
|View full text |Cite
|
Sign up to set email alerts
|

Impaired sodium-dependent adaptation of arterial stiffness in formerly preeclamptic women: the RETAP-vascular study

Abstract: van der Graaf AM, Paauw ND, Toering TJ, Feelisch M, Faas MM, Sutton TR, Minnion M, Lefrandt JD, Scherjon SA, Franx A, Navis G, Lely AT. Impaired sodium-dependent adaptation of arterial stiffness in formerly preeclamptic women: the RETAP-vascular study. Am J Physiol Heart Circ Physiol 310: H1827-H1833, 2016. First published April 8, 2016; doi:10.1152/ajpheart.00010.2016.-Women with a history of preeclampsia have an increased risk for cardiovascular diseases later in life. Persistent vascular alterations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…As in the previous study, the difference between groups in PWV was not dependent on BP levels. In a number of studies involving hypertensive patients [97,98,99,100], aortic PWV values were significantly lower in the low-salt group than in the high-salt group; however, other studies in which no significant difference in PWV has been described in relation to dietary sodium intake can be found in the literature [101,102,103,104,105,106,107]. In almost all of these latter randomized controlled trials, however, the relatively small number of enrolled patients and the relatively short duration of a given level of sodium intake with the diet assigned to each group were probably the main factors affecting the failure in reaching a statistically significant difference in PWV between high- and low-salt groups.…”
Section: Sodium Intake and Arterial Stiffnessmentioning
confidence: 99%
“…As in the previous study, the difference between groups in PWV was not dependent on BP levels. In a number of studies involving hypertensive patients [97,98,99,100], aortic PWV values were significantly lower in the low-salt group than in the high-salt group; however, other studies in which no significant difference in PWV has been described in relation to dietary sodium intake can be found in the literature [101,102,103,104,105,106,107]. In almost all of these latter randomized controlled trials, however, the relatively small number of enrolled patients and the relatively short duration of a given level of sodium intake with the diet assigned to each group were probably the main factors affecting the failure in reaching a statistically significant difference in PWV between high- and low-salt groups.…”
Section: Sodium Intake and Arterial Stiffnessmentioning
confidence: 99%
“…Eight hundred and twenty-five (825) citations were identified through a systematic search-of which, 782 were excluded on the basis of title/abstract. The most common exclusion criteria were: language (42), duplicates-same cohort (27), different research subject (516), not original articles (191), sample size <100 subjects for observational studies only (6). Forty-three (43) articles were then assessed for eligibility and five were excluded due to irrelevant research subject and two due to different studying parameter (Na/K ratio).…”
Section: Number Of Studies Screened and Selectedmentioning
confidence: 99%
“…Thirty-one (31) studies examining arteriosclerosis were identified-of which, 14 were observational [15][16][17][18][19][20][27][28][29][30][31][32][33][34] and 17 were interventional [22,23,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Studies Investigating Arteriosclerosis (Arterial Stiffness)mentioning
confidence: 99%
See 2 more Smart Citations